Bionic electrothermal coupling composite material, medical suit and use based on pyroelectric effect
By combining bionic electrothermal coupled composite materials with pyroelectric effect in photothermal therapy, dopamine-encapsulated inorganic photosensitive particles and piezoelectric polymers, the macrophage polarization mechanism and insufficient material performance in photothermal therapy are solved. The problem has achieved improved tissue repair and healing effects.
Patent Information
- Application Number
- CN202410494067.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-24
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-04-24
AI Technical Summary
The existing photothermal therapy technology is unclear in regulating macrophage polarization mechanism, and the long-term performance of charged materials after implantation into the body is insufficient, making it difficult to effectively promote tissue repair and healing.
Develop a bionic electrothermal coupled composite material based on the pyroelectric effect. By combining dopamine-encapsulated inorganic photosensitive particles with piezoelectric polymers, it forms a membrane material that can generate an electrothermal coupling effect under near-infrared light irradiation, which is used to regulate immune cell poles. and promote organizational restoration.
The synergistic effect of the electrical and thermal properties of materials is achieved, promoting the differentiation of macrophages from M1 to M2, improving the tissue repair and healing effect, and solving the problem of insufficient long-term performance of charged materials.
Smart Images

Figure CN118079098B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photothermal therapy and pyroelectric effect combination, and in particular to an electrothermal bionic coupling composite material based on the pyroelectric effect and its use in promoting tissue repair or healing. Background Art
[0002] At present, the application of photothermal therapy technology in immunity is mainly limited to regulating the immune microenvironment of tumor cells. Among the various external stimuli for targeted regulation, near-infrared light (NIR) stands out due to its high tissue penetration ability, minimal damage to normal tissues, and easy remote control, and has become one of the important means of current photothermal therapy. De Matteis et al. used NIR to induce the photothermal effect of AuNP, which can reduce the release of macrophage inflammatory factors while achieving better anti-tumor effects.
[0003] The mechanism of the effect of photothermal therapy on macrophage polarization is still unclear. Heat shock proteins (HSPs) are believed to play an important role in the process of cell response to external stimuli such as high temperature and ultraviolet rays. Catozzi et al.'s study showed that 41°C heat stimulation increased the expression of monocyte HSP70 and promoted the polarization of cells from classically activated M1 type to non-classically activated M2 type. Zhang et al. used whole genome technology to detect the mechanism of the photothermal properties of AuPd nanomaterials on the osteogenic differentiation of MC3T3 cells and found that Wnt and Ca2+ upregulated expression mainly by HSPs and BMP2. 2+ The signaling pathway is activated. Other studies have reported that overexpression of HSPA1A (HSP70 homolog) promotes osteogenic differentiation of MSCs and is closely related to the Wnt / β-catenin signaling pathway. The above studies suggest that HSPs proteins, Ca 2+ and Wnt / β-catenin signaling pathways may play an important role in the cellular response to the photothermal properties of materials.
[0004] The information in the background technology is only for illustrating the general background of the present invention and should not be regarded as admitting or suggesting in any form that such information constitutes the prior art known to a person skilled in the art. Summary of the invention
[0005] In order to solve at least some of the technical problems in the prior art, the present invention provides a bionic electrothermal coupling composite material based on pyroelectric effect and its use for promoting tissue repair and / or healing. Specifically, the present invention includes the following contents.
[0006] In a first aspect, the present invention provides a bionic electrothermal coupling composite material based on the pyroelectric effect, which comprises a polymer and inorganic photosensitive particles dispersed therein, wherein the polymer is selected from piezoelectric polymers, and the inorganic photosensitive particles are inorganic fine particles wrapped with dopamine.
[0007] The second aspect of the present invention provides a method for preparing a bionic electrothermal coupling composite material based on the pyroelectric effect, which comprises:
[0008] The step of providing an inorganic photosensitive particle dispersion and a piezoelectric polymer solution;
[0009] The step of mixing the dispersion liquid with the piezoelectric polymer solution to obtain a suspension; and
[0010] Steps for preparing membrane material using suspension.
[0011] According to a third aspect of the present invention, there is provided a medical kit for tissue repair or healing, comprising an energy generating unit and an energy receiving unit, wherein the energy generating unit is configured to generate light energy, the energy receiving unit comprises the composite material described in the first aspect, and is configured to be implanted in a body or disposed on the surface of a body, and can generate an electrothermal coupling effect when receiving light energy that passes through tissue to reach the energy receiving unit in the body.
[0012] In certain embodiments, according to the medical kit of the third aspect, the polymer is selected from at least one of polyvinylidene fluoride, polyvinylidene fluoride-trifluoroethylene copolymer, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-tetrafluoroethylene copolymer, polymethyl methacrylate, polydimethylsiloxane and poly(L-lactic acid).
[0013] In certain embodiments, according to the medical kit of the third aspect, the inorganic photosensitive particles are nanoscale ceramic particles.
[0014] In certain embodiments, according to the medical kit of the third aspect, the nano-scale ceramic particles are selected from at least one of barium titanate, barium strontium titanate, strontium titanate, lithium niobate, and potassium sodium niobate.
[0015] In certain embodiments, according to the medical kit of the third aspect, the energy generating unit is configured as a laser capable of generating continuous light and / or pulsed light.
[0016] A fourth aspect of the present invention provides use of a composite material in preparing a medical kit for tissue repair or healing, wherein the composite material is a bionic electrothermal coupling composite material based on pyroelectric effect according to the first aspect.
[0017] A fifth aspect of the present invention provides a method for regulating the polarization of immune cells using a bionic electrothermal coupling composite material based on the pyroelectric effect, which comprises the following steps:
[0018] (1) a step of constructing a culture system using immune cells and composite materials; and
[0019] (2) a step of subjecting the culture system to light treatment;
[0020] Wherein, the composite material includes a polymer and inorganic photosensitive particles dispersed therein; the light treatment includes irradiating the composite material with near-infrared light, and the light treatment includes continuous light treatment and / or pulsed light treatment; the regulation is to promote the differentiation of macrophages from M1 to M2.
[0021] In certain embodiments, the regulation refers to upregulating IL-10 expression in immune cells or increasing the proportion of CD206-positive cells in an immune cell population.
[0022] The sixth aspect of the present invention provides an immune cell obtained by the method described in the fifth aspect.
[0023] The present invention establishes a correlation between the electrical and thermal properties of materials, and realizes the bionic coupling of the electrothermal effect of materials. Through coupling, the piezoelectric properties and the pyroelectric effect work synergistically to achieve the effect of promoting macrophage polarization and promoting tissue repair or healing. In an exemplary embodiment, the charging performance of the material can be improved by non-invasively manipulating near-infrared light in vitro, realizing on-demand power supply based on the near-infrared field, and solving the problem of insufficient long-term performance of charged materials after implantation in the body. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The films composed of different materials are at 0.6W cm -2 Heating curves under 808 nm laser irradiation under different power conditions.
[0025] Figure 2 UV-visible absorption spectra of films composed of different materials.
[0026] Figure 3 It is the UV-visible light absorbance value of the film composed of different materials at a wavelength of 808nm.
[0027] Figure 4 Infrared thermal imaging photographs of films composed of different materials under 808 nm laser irradiation for different time periods (0, 1, 5, 10, 15 and 30 mins from left to right).
[0028] Figure 5 The pyroelectric coefficient of the polarized composite film material changes with temperature in the temperature range of 35-45°C.
[0029] Figure 6 CD206 immunofluorescence staining results and quantitative statistical graphs obtained after macrophages were cultured with nanocomposites under continuous / pulsed illumination. Figure 6In b, the columns from left to right are polarization group, unpolarized group, continuous NIR+polarization group, and interval NIR+polarization group. Figure 6 c includes three groups of column charts of IL-10, TNF-α, and IL-b. In each group, the columns from left to right are polarized group, unpolarized group, continuous NIR+polarized group, and interval NIR+polarized group. Figure 6 The d includes three groups of column charts of IL-10, TNF-α, and IL-b. In each group, the columns from left to right are polarized group, unpolarized group, continuous NIR+polarized group, and interval NIR+polarized group.
[0030] Figure 7 On the third day, the expression of CD86 and CD206 of macrophages on the materials under different stimulation conditions were detected by flow cytometry and quantitatively analyzed.
[0031] Figure 8 Skin wound healing under different stimulation conditions.
[0032] Fig. 9 Micro-CT analysis and quantitative results of the defect area 4 weeks after material implantation.
[0033] Fig.10 Results of in vivo macrophage analysis after material implantation.
[0034] Fig.11 The polarization results of macrophages in vitro simulated in vivo experiments. DETAILED DESCRIPTION
[0035] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0036] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that the upper and lower limits of the scope and each intermediate value therebetween are specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0037] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0038] [Composite Materials]
[0039] In one aspect of the present invention, a bionic electrothermal coupling composite material based on pyroelectric effect is provided, which comprises a polymer and inorganic photosensitive particles dispersed therein, wherein the polymer is selected from piezoelectric polymers, and the inorganic photosensitive particles are inorganic fine particles wrapped by dopamine.
[0040] In the present invention, bionic electrothermal coupling refers to the synergistic effect of piezoelectric effect and pyroelectric effect, which can greatly promote the repair and / or healing of tissues in the body.
[0041] In the present invention, piezoelectric polymer refers to a crystalline polymer material that generates a voltage between the two end faces when subjected to pressure, and examples thereof include but are not limited to polyvinylidene fluoride, polyvinylidene fluoride-trifluoroethylene copolymer, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-tetrafluoroethylene copolymer, polymethyl methacrylate, polydimethylsiloxane, and polylactic acid. The present invention may use one of the above polymers, or a combination of two or more thereof.
[0042] In the present invention, inorganic photosensitive particles refer to particles that are sensitive to light, and in particular, particles that can gather heat energy after receiving infrared light. Inorganic photosensitive particles are generally modified particles, which illustratively include an inorganic core and a polydopamine layer.
[0043] In certain embodiments, the inorganic photosensitive particles of the present invention are obtained by dispersing nano-scale ceramic particles in an aqueous solution of dopamine hydrochloride, heating and stirring the reaction, washing and drying. When preparing inorganic photosensitive particles, the dosage ratio of dopamine hydrochloride to nano-scale ceramic particles is important. Generally speaking, the weight ratio of dopamine hydrochloride to nano-scale ceramic particles is 1:10-1:30, that is, based on 1 part by weight of dopamine hydrochloride, the nano-scale ceramic particles are 10-30 parts by weight, preferably 12-28 parts by weight, and more preferably 14-26 parts by weight, such as 15 parts by weight and 23 parts by weight. If the dosage of dopamine hydrochloride is too little, the photosensitivity of the obtained particles tends to decrease, and even the aggregation and heat absorption function required for pyroelectricity cannot be achieved. On the other hand, if the dosage of dopamine hydrochloride is too much, the thickness of the polydopamine on the surface of the obtained particles becomes larger, affecting the piezoelectric properties.
[0044] When preparing inorganic photosensitive particles, it is advisable to control the heating and stirring reaction conditions to form a polydopamine layer with a thickness of 25-50 μm on the surface of the nano-ceramic particles. For this purpose, the reaction temperature is generally controlled to be 40-80°C and the reaction time is 5-20 hours during the heating and stirring reaction. Optionally, the reaction temperature is, for example, 50°C, 60°C, 65°C, 70°C, 75°C, etc. Optionally, the reaction time is 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, etc. Those skilled in the art can freely select the specific temperature and time within the above range. Preferably, it further includes a step of using an ultrasonic treatment dispersion before the heating and stirring reaction. The ultrasonic treatment time can be 10 minutes to 1 hour, so that the nano-ceramic particles are dispersed more evenly.
[0045] When preparing inorganic photosensitive particles, optionally, the step of washing the obtained nano-scale ceramic particles coated with the polydopamine layer is further included. Water and alcohol can be used for washing, and generally multiple washings are required. Exemplarily, water is used for washing first, and then alcohol is used for washing. Washing can be performed multiple times.
[0046] When preparing the inorganic photosensitive particles, optionally, a step of drying the washed particles is further included, preferably by heating, and the heating temperature can be, for example, 40-60°C, preferably 45-55°C.
[0047] When preparing the inorganic photosensitive particles, optionally, further comprising the step of dissolving dopamine hydrochloride in a solvent. The solvent herein comprises an aqueous solvent. The concentration of dopamine hydrochloride is controlled to be 0.5-5 mg / ml, such as 0.8 mg / ml, 1 mg / ml, 1.5 mg / ml, 2 mg / ml, 2.5 mg / ml, 3 mg / ml, 3.5 mg / ml, 4 mg / ml, 4.5 mg / ml. Too high or too low a concentration is not conducive to obtaining high photosensitivity.
[0048] In the present invention, the nano-scale ceramic particles are not particularly limited, and examples thereof include, but are not limited to, barium titanate, barium strontium titanate, strontium titanate, lithium niobate, and potassium sodium niobate. The present invention may use one of the above substances or a combination of two or more thereof.
[0049] [Preparation method]
[0050] Another aspect of the present invention provides a method for preparing a bionic electrothermal coupling composite material based on the pyroelectric effect, which includes the steps of providing an inorganic photosensitive particle dispersion and a piezoelectric polymer solution; mixing the dispersion with the piezoelectric polymer solution to obtain a suspension; and preparing a membrane material using the suspension.
[0051] In the present invention, the amount of inorganic photosensitive particles and solvent in the inorganic photosensitive particle dispersion is not limited, generally 40-100 mg / ml, preferably 45-80 mg / ml, such as 50 mg / ml, 60 mg / ml, 70 mg / ml, etc. Examples of the solvent include but are not limited to N,N-dimethylformamide, etc. When preparing the dispersion, it is preferred to promote dispersion by stirring or ultrasound.
[0052] In the present invention, the concentration of the polymer in the piezoelectric polymer solution is generally 10-100 mg / ml, preferably 20-80 mg / ml, more preferably 25-60 mg / ml, such as 30 mg / ml, 40 mg / ml, 50 mg / ml, 60 mg / ml and the like.
[0053] The present invention further includes a step of treating the suspension, wherein the suspension is placed in a vacuum drying oven for vacuum degassing. In addition, in order to prevent impurities from being doped, when preparing the membrane material, the substrate such as a quartz glass plate is cleaned with anhydrous ethanol, pure water, etc. After the quartz glass plate is completely dried, the suspension is poured on it, and the thickness is made uniform with a scraper of a drooling machine.
[0054] The present invention further includes a step of volatilizing the solvent. For example, the step includes placing a quartz glass plate horizontally on a heating platform in a fume hood and heating at 30-65° C. for 5 hours to completely volatilize the solvent. The thickness of the membrane material finally obtained in the present invention is generally 20-50 μm, 25 μm, 30 μm, or 35 μm.
[0055] In certain embodiments, the preparation method of the present invention further comprises the step of polarizing the composite material. Exemplary parameters of the polarization treatment include, but are not limited to: the polarization medium is one of air and methyl silicone oil, the polarization voltage is 1 kV-30 kV, the distance between the pole head and the sample is set to be 1 mm-50 mm, the polarization temperature is 25°C-100°C, and the polarization time is 1 minute-60 minutes.
[0056] In certain embodiments, the preparation method of the present invention further comprises an annealing treatment. An exemplary annealing treatment comprises subjecting the composite film to 80-150° C. treatment for 5-30 minutes. The annealing temperature may be, for example, 85° C., 90° C., 95° C., 100° C., 120° C., 140° C., etc.
[0057] [Medical kit for tissue repair or healing]
[0058] In another aspect of the present invention, a medical kit for tissue repair or healing is provided, which includes an energy generating unit and an energy receiving unit, wherein the energy generating unit is configured to generate energy light, in particular, energy light that can pass through tissue, and the energy receiving unit comprises the composite material as described above, and is configured to be implanted in the body or disposed on the surface of the tissue, and when in the body, it is capable of receiving energy light that passes through the tissue to reach the energy receiving unit to generate an electrothermal coupling effect. Exemplarily, the energy receiving unit is configured to increase its temperature to 35-45°C, preferably 41°C, after receiving energy. The present invention finds that when the temperature of the energy receiving unit reaches this range, it has the best tissue repair and healing effect.
[0059] In the present invention, the energy generating unit comprises a laser. Generally speaking, the laser of the present invention is configured to generate energy, such as light, that penetrates tissues such as skin tissue and enters the body. In particular, a near-infrared laser, such as a 600-1000nm near-infrared laser. The laser can generate near-infrared laser continuously or in a pulsed manner. Preferably, the laser of the present invention can automatically generate pulsed near-infrared laser, and the pulse frequency is not limited and can be freely set as required. For this purpose, the laser can be provided with, for example, a timer and a control unit, thereby controlling the generation of pulsed laser.
[0060] In the present invention, the energy receiving unit comprises the composite material of the present invention, in particular the composite film. The composite material has been described in detail above and will not be described again here. The energy receiving unit can preferably be configured to be implanted inside or on the surface of a body and to receive energy generated by the energy generating unit, in particular light energy.
[0061] In the present invention, the medical set includes a combination of an energy generating unit and an energy receiving unit. The number of energy generating units and energy receiving units is not limited. One energy generating unit may correspond to multiple energy generating units in one medical set, or multiple energy generating units and multiple energy receiving units may be included in one medical set. Exemplarily, the energy generating unit in the medical set may be used repeatedly, or different units in different medical sets may be combined or used in conjunction with each other when used. For example, the energy generating unit of the first medical set is used in combination with the energy receiving unit in the second medical set.
[0062] In the present invention, tissue repair or healing includes repair of soft tissues such as skin tissue, and also includes repair or healing of bone tissue, especially repair or regeneration after bone defect.
[0063] [Methods for regulating immune cell polarization]
[0064] In another aspect of the present invention, a method for regulating the polarization of immune cells using a bionic electrothermal coupling composite material based on the pyroelectric effect is provided, which comprises the following steps:
[0065] (1) a step of constructing a culture system using immune cells and composite materials; and
[0066] (2) A step of subjecting the culture system to light treatment.
[0067] In the present invention, the composite material has been described in detail above and will not be described again here.
[0068] In the present invention, light treatment refers to irradiating the composite material with near-infrared light, and the light treatment includes continuous light treatment and / or pulsed light treatment. The conditions of continuous light treatment and / or pulsed light treatment are preferably such that the temperature of the treated area is raised to the required temperature. The required temperature here is generally 35-45°C, such as 37°C, 40°C, 42°C, 44°C and 45°C. For this purpose, the pulsed light treatment conditions of the present invention include, for example, irradiation for 1-20 minutes, intervals of 0.5-20 minutes, repeated once or multiple times as needed.
[0069] In the present invention, regulation includes promoting or initiating the differentiation of immune cells from M1 to M2. The polarization of the present invention can be optionally an in vitro method, thereby preparing M2 polarized immune cells. In the present invention, immune cells are not limited, and examples thereof include but are not limited to macrophages.
[0070] In the present invention, the culture system comprises a composite material and a suitable culture medium. The culture medium is known in the art, and commercially available products can be used.
[0071] Example
[0072] 1. Design and construction of bionic electrothermal coupling effect
[0073] The electrothermal binary physical property nanocomposite system was designed and constructed. The composite material was prepared with piezoelectric polymer polyvinylidene fluoride-trifluoroethylene P (VDF-TrFE) as the matrix and polydopamine (PDA) wrapped BTO as the filler. The specific steps include:
[0074] 1. Preparation of PDA@BTO / P(VDF-TrFE) nanocomposite membrane
[0075] Weigh a certain amount of dopamine hydrochloride particles and dissolve them in pure water. Stir for 10 minutes in a 60°C water bath to completely dissolve them. Weigh a certain amount of barium titanate BTO nanopowder and put it into the dopamine hydrochloride aqueous solution for ultrasonication. Continue to heat in a 60°C water bath and stir overnight. After standing and stratification, absorb the supernatant, wash with pure water and anhydrous ethanol alternately for 3 times to make the supernatant clear, pour out the supernatant and place it in a constant temperature drying oven (55°C) to obtain dry dopamine-coated BTO nanopowder.
[0076] Weigh a certain mass of PDA-coated BTO nanopowder, dissolve it in DMF, and stir ultrasonically to evenly disperse the nanopowder. At the same time, weigh a certain mass of P(VDF-TrFE) polymer particles, dissolve it in DMF and stir. Mix and stir the two liquids evenly, cover the beaker with plastic wrap to prevent volatilization, stir overnight to obtain a uniform and stable suspension, and then put it into a vacuum drying oven to evacuate and remove bubbles. To prevent impurity doping, clean the quartz glass plate with anhydrous ethanol, pure water, etc. After the quartz glass plate is completely dry, pour the suspension on it, use a scraper of a salivating machine to make the thickness uniform, place the quartz glass plate horizontally on the heating platform in the fume hood, keep heating at 55°C to completely evaporate the solvent, and finally obtain a nano piezoelectric composite film with a thickness of 30 microns.
[0077] 2. Polarization of PDA@BTO / P(VDF-TrFE) nanocomposite films
[0078] The prepared materials were cut into a size of 40×40 mm and placed flatly on the metal plate of the corona polarization instrument. The electrode tip was adjusted to be 20 mm above the center of the material. The loading voltage was adjusted to 13 kV. The polarization time for each material was 30 minutes at room temperature.
[0079] 3. In vitro material photothermal performance test
[0080] The PDA@BTO / P(VDF-TrFE) nanocomposite film material was cut into a size of 40×40 mm and fixed in a homemade device to ensure that the material was flat and there was no other obstruction on the upper and lower surfaces of the material to avoid affecting the accuracy of the measurement. The probe of the 808 nm near-infrared laser transmitter was fixed directly below the PDA@BTO / P(VDF-TrFE) nanocomposite film to ensure that the laser could accurately and evenly irradiate the nanocomposite film material. The camera of the thermal imaging instrument was aimed at the nanocomposite film material, and the different powers of the 808 nm near-infrared laser transmitter were adjusted to monitor the temperature change of the material after irradiation with 808 nm near-infrared light in real time, and the temperature was recorded and analyzed on the software.
[0081] In order to simulate the temperature rise performance of the PDA@BTO / P(VDF-TrFE) nanocomposite membrane implanted in the surface of animal bone defects, the equipment was placed in a 37°C incubator during the in vitro temperature rise test, and the near-infrared irradiation experiment was performed when the surface temperature of the material reached 37°C using a thermal imager. When the PDA@BTO / P(VDF-TrFE) nanocomposite membrane repairs bone defects in animals, there will be tissue fluid in the defect area. To simulate this phenomenon, the equipment was placed in a 37°C incubator during the in vitro temperature rise test and a small amount of PBS solution was added to the surface of the material. The near-infrared irradiation experiment was performed when the surface water temperature of the material reached 37°C using a thermal imager. The other control group materials were measured according to the above method.
[0082] 2. Thermal properties of composite materials
[0083] Figure 1 The heating curves of films composed of different materials under 808 nm laser irradiation under certain power conditions are shown in Figure 2. Figure 1 It can be seen that under a certain light power, the temperature of the polarized and unpolarized PDA-BTO / P(VDF-TrFE) nanocomposite films can be raised to the target temperature of about 40°C in vitro within 1 minute; and this temperature can be maintained.
[0084] Figure 2 UV-visible absorption spectra of films composed of different materials.
[0085] Figure 3 is the UV-visible light absorbance value of films composed of different materials at a wavelength of 808nm. Figure 3 It can be seen that the UV-visible near-infrared spectrum shows that PDA-BTO / P(VDF-TrFE) has the desired absorption in the NIR-I region at 808 nm.
[0086] Figure 4 Infrared thermal imaging photographs of films composed of different materials under 808 nm laser irradiation for different time periods (0, 1, 5, 10, 15 and 30 mins from left to right).
[0087] 3. Electrical properties of composite materials
[0088] When the PDA@BTO / P(VDF-TrFE) nanocomposite film material is subjected to corona polarization, it shows polarization phenomenon on a macro scale, and its temperature change will produce pyroelectric effect. According to the following, the best temperature for promoting bone tissue treatment is 42℃, and the maximum heating temperature cannot exceed 43℃, so the pyroelectric coefficient of the polarized composite film material in the temperature range of 35-45℃ is observed as a function of temperature ( Figure 5 ). It can be seen that in the temperature range of 35-45°C, the pyroelectric coefficients of PDA@BTO / P(VDF-TrFE) nanocomposite film, BTO / P(VDF-TrFE) nanocomposite film, and P(VDF-TrFE) nanocomposite film at the same temperature are in descending order. Among them, the pyroelectric coefficient of PDA@BTO / P(VDF-TrFE) nanocomposite film is much higher than that of other composite films. At 42°C, the pyroelectric coefficients of PDA@BTO / P(VDF-TrFE) nanocomposite film, BTO / P(VDF-TrFE) nanocomposite film, and P(VDF-TrFE) nanocomposite film are 89.1, 5.37, and -0.939 (μC / m 2℃). With the increase of temperature, the pyroelectric coefficient increases in the temperature range of 35-45℃. This shows that when the temperature of the material changes, the internal polarization intensity of the material also changes, causing the bound charge density to change.
[0089] 4. Effects of composite materials on immune cell polarization
[0090] BMDM macrophages were inoculated on the PDA@BTO / P(VDF-TrFE) nanocomposite membrane overnight to allow the cells to completely adhere to the surface of the material. The polarized PDA@BTO / P(VDF-TrFE) nanocomposite membrane group was subjected to near-infrared irradiation. The whole process was in the cell culture incubator. The radiation wavelength was 808 nm. The laser power and the distance of the laser irradiation material were adjusted. The pulsed light irradiation was: 10 minutes per well, 5 minutes between each irradiation, and a total of 3 cycles. The continuous light irradiation was: 30 minutes per well. After the near-infrared irradiation, the macrophages continued to be cultured in a 37°C cell incubator. The camera of the thermal imaging instrument was aimed at the six-well plate to monitor the temperature changes after 808 nm near-infrared light irradiation in real time, and the elevated temperature was maintained between 3-4°C.
[0091] like Figure 6 As shown, (ab) CD206 immunofluorescence staining results and quantitative statistical graphs of macrophages cultured with PDA@BTO / P(VDF-TrFE) nanocomposites for one day and irradiated with continuous / pulsed light for 0.5 h; (c) M1 and M2 polarization-related gene expression of macrophages cultured with PDA@BTO / P(VDF-TrFE) nanocomposites for one day and irradiated with continuous / pulsed light for 0.5 h; (d) M1 and M2 polarization-related gene expression of macrophages cultured with PDA@BTO / P(VDF-TrFE) nanocomposites for seven days and irradiated with continuous / pulsed light for 0.5 h.
[0092] In addition, the present invention also tested the expression of CD86 and CD206 of macrophages on the material under different stimulation conditions on the third day and conducted quantitative analysis. Figure 7 shown. Figure 7 In each column, from left to right, they are UN, N-30, N-3*10, and N-6*5. Among them, UN means no irradiation and no temperature increase; N-30 means polarization and continuous illumination for 30 minutes; N-3*10 means illumination for 10 minutes (41°C), stop for 5 minutes, and cycle 3 times; N-6*5 means illumination for 5 minutes (41°C), stop for 5 minutes, and cycle 6 times. In vitro results show that when the light-maintained temperature rises to about 41°C, macrophages transform from M1 (CD86) to M2 (CD206).
[0093] 5. Research on composite materials for wound healing
[0094] Figure 8 The wound healing status under different stimulation conditions. Figure 8 UN means no irradiation and no temperature increase; N-30 means continuous irradiation for 30 minutes, keeping the temperature at 41°C; N-3*10 means irradiation for 10 minutes (41°C), stop for 5 minutes, and cycle 3 times; N-6*5: irradiation for 5 minutes (41°C), stop for 5 minutes, and cycle 6 times.
[0095] VI. Research on the regulation of bone immune microenvironment by composite materials to promote the healing of critical bone defects
[0096] A 5 mm critical bone defect model of SD rat skull was constructed. Flow cytometry and immunofluorescence techniques were used to evaluate the immune responses, such as macrophage adhesion, polarization phenotype, and cytokine release in the local tissue fluid and on the tissue surface of the covering material in the early stage of healing. Micro-CT and tissue sections were used to evaluate the osteogenesis. The bionic electro-thermal coupling effect of PDA@BTO / P(VDF-TrFE) nanocomposite materials on the regulation of the immune microenvironment and its effect on promoting bone defect healing were studied in animals.
[0097] Fig. 9 The micro-ct analysis and quantitative results of the defect area 4 weeks after the material was implanted. To explore the regulatory effect of electrothermal coupling on bone defect repair, the near-infrared irradiation temperature was designed to increase by 4°C, the frequency was 10 minutes of illumination, 5 minutes of rest, and 3 cycles. The design groups were blank group (UP), pure illumination group (N+UP), polarization group (P), illumination + polarization group (N+P). The results of animal osteogenesis under these different stimuli are as follows Fig. 9 As shown, the 4w illumination + polarization group had better bone formation effect than other groups.
[0098] Fig.10 The results of macrophage analysis in vivo after material implantation. (A) shows the expression and quantitative analysis of CD86 and CD206 in the tissue fluid of the defect area by flow cytometry; (B) shows the results and quantitative analysis of CD206 and CD86 immunofluorescence of macrophages on the material seven days after implantation into the defect area.
[0099] In the results of electrothermal coupling regulation of the early immune response of bone defects in vivo, flow cytometry and immunofluorescence results showed that pulsed electrothermal coupling of PDA-BTO / P(VDF-TrFE) material in vivo animal experiments could promote the differentiation of macrophages M1 (CD86) type in the early immune response, and promote the transformation of M1 to M2 (CD206) type in the late immune response, compared with electrical stimulation or thermal stimulation alone.
[0100] Fig.11The results of macrophage polarization in vitro simulated in vivo experiments. In the in vitro simulated in vivo experiments, the electrothermal coupling of PDA-BTO / P (VDF-TrFE) material promoted macrophage M1 polarization on the first day and M2 transformation on the seventh day compared with electrical stimulation and thermal stimulation alone, which is the same as in vivo. The electrothermal coupling of PDA-BTO / P (VDF-TrFE) material upregulated the expression of osteogenesis-related genes on day 4 compared with electrical stimulation and thermal stimulation alone. Fig.11 Middle: (A) CD206 and CD86 immunofluorescence results of macrophages on the materials under different stimulation conditions; (B) Quantitative analysis of CD206 and CD86 immunofluorescence of macrophages on the materials under different stimulation conditions, from left to right are UP group, N+UP group, P group and N+P group; (C) Expression of CD86 and CD206 by flow cytometry of macrophages on the materials under different stimulation conditions; (D) Quantitative analysis of CD86 and CD206 by flow cytometry of macrophages on the materials under different stimulation conditions. For CD86 and CD206 groups, from left to right are UP group, N+UP group, P group and N+P group; (E) Expression of M1 and M2 polarization-related genes of macrophages on the materials under different stimulation conditions. Among them, for CD206, IL-10, Fizz-1, INOS, and 7NF-a, from left to right are UP group, N+UP group, P group, and N+P group; (F) BMP2 immunofluorescence results of osteogenic-related gene expression of bone marrow mesenchymal stem cells on the material under different stimulation conditions on the fourth day; (G) BMP2 immunofluorescence quantitative analysis of osteogenic-related gene expression of bone marrow mesenchymal stem cells on the material under different stimulation conditions on the fourth day, from left to right are UP group, N+UP group, P group, and N+P group; (H) Quantitative analysis of osteogenic-related gene expression of bone marrow mesenchymal stem cells on the material under different stimulation conditions on the fourth day. Among them, for ALP, OPN, RUNX2, and BMP2, from left to right are UP group, N+UP group, P group, and N+P group.
[0101] Although the present invention has been described with reference to exemplary embodiments, it should be understood that the present invention is not limited to the disclosed exemplary embodiments. Various adjustments or changes may be made to the exemplary embodiments of the present specification without departing from the scope or spirit of the present invention. The scope of the claims should be based on the broadest interpretation to cover all modifications and equivalent structures and functions.
Claims
1. A medical kit for repairing or healing bone defects, characterized in that: The energy generating unit comprises an energy receiving unit, wherein the energy generating unit is configured to generate a laser capable of generating pulsed light, the energy receiving unit comprises a bionic electrothermal coupling composite material based on the pyroelectric effect, and is configured to be implanted in a body or disposed on a body surface, and generates an electrothermal coupling effect when receiving pulsed light treatment, wherein the pulsed light treatment comprises irradiating with a 600-1000nm near-infrared laser for 1-20 minutes, with an interval of 0.5-20 minutes, and repeating once or multiple times, so that the temperature of the treated area is 42°C; The bionic electrothermal coupling composite material is obtained by a method comprising the following steps: (1) providing an inorganic photosensitive particle dispersion and a piezoelectric polymer solution, which comprises: Weigh dopamine hydrochloride particles and dissolve them in pure water. Stir for 10 minutes while heating in a water bath at 60°C to completely dissolve them. Weigh barium titanate nanopowder and put it into a dopamine hydrochloride aqueous solution for ultrasonication. Continue heating in a water bath at 60°C and stirring overnight. After standing for stratification, absorb the supernatant, wash it alternately with pure water and anhydrous ethanol to make the supernatant clear, pour out the supernatant and dry it at a constant temperature to obtain dry polydopamine-coated barium titanate nanopowder. Weigh the polydopamine-coated barium titanate nanopowder and dissolve it in N,N-dimethylformamide. Stir ultrasonically disperse the nanopowder to obtain an inorganic photosensitive particle dispersion. At the same time, weigh polyvinylidene fluoride-trifluoroethylene copolymer particles and dissolve them in N,N-dimethylformamide and stir to obtain a piezoelectric polymer solution, wherein the weight ratio of the dopamine hydrochloride to the barium titanate nanopowder is 1:10-1:
30. (2) the step of mixing the inorganic photosensitive particle dispersion with the piezoelectric polymer solution to obtain a suspension and the step of using the suspension to prepare a membrane material, which comprises: mixing the inorganic photosensitive particle dispersion of step (1) with the piezoelectric polymer solution and stirring them uniformly, stirring overnight to obtain a uniform and stable suspension, vacuuming to remove bubbles, cleaning the quartz glass plate to prevent impurity doping, pouring the suspension on the quartz glass plate after it is completely dried, using a scraper of a salivation machine to make the thickness uniform, placing the quartz glass plate horizontally on a heating platform in a fume hood, and heating at 55°C to completely evaporate the solvent to obtain a composite film; (3) further comprising performing polarization treatment and annealing treatment on the composite film of step (2), wherein the polarization treatment conditions include: the polarization medium is one of air and methyl silicone oil, the polarization voltage is 1 kV-30 kV, the distance between the pole head and the sample is set to be 1 mm-50 mm, the polarization temperature is 25°C-100°C, the polarization time is 1 minute-60 minutes, and the annealing treatment includes placing the composite film at 80-150°C for 5-30 minutes.
2. A method for regulating the polarization of immune cells using a bionic electrothermal coupling composite material based on pyroelectric effect, characterized in that: It includes the following steps: (1) A step of constructing a culture system using immune cells and composite materials; and (2) a step of subjecting the culture system to light treatment; Wherein, the composite material comprises a polymer and inorganic photosensitive particles dispersed therein; the light treatment comprises irradiating the composite material with near-infrared light, and the light treatment comprises irradiating with a 600-1000nm near-infrared laser for 1-20 minutes, with an interval of 0.5-20 minutes, and repeating one or more times for pulse light treatment, the polymer is selected from at least one of polyvinylidene fluoride, polyvinylidene fluoride-trifluoroethylene copolymer, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-tetrafluoroethylene copolymer, polymethyl methacrylate, polydimethylsiloxane and L-polylactic acid, and the inorganic photosensitive particles are nano-scale ceramic particles wrapped with polydopamine; the regulation is to promote the differentiation of macrophages from M1 to M2 type; The nano-scale ceramic particles are selected from at least one of barium titanate, barium strontium titanate, strontium titanate, lithium niobate and potassium sodium niobate.
3. The method according to claim 2, characterized in that The composite material is obtained by the following steps, including: The step of providing an inorganic photosensitive particle dispersion and a piezoelectric polymer solution; The step of mixing the inorganic photosensitive particle dispersion and the piezoelectric polymer solution to obtain a suspension; and The invention relates to a step of preparing a membrane material by using the suspension.
Citation Information
Patent Citations
Piezoelectric active bone repair composite material and preparation method thereof
CN104208754A
Barium titanate-graphene composite material as well as preparation method and application thereof
CN114732906A